Investigating EFL Learners’ Lacks in Writing - LAICHE , Sara; NEMOUCHI , Abdelhak (Journal of Human Sciences, 2023)
Writing plays a critical role in social, professional, and academic frames especially in Foreign Language Learning (FLL), which usually entails the learners’ exposure to the language skills that are listening, speaking, reading, and writing. However, learning to write accurately is not an easy task in which it necessitates considerable practice and guidance. Although teachers often support their learners to enhance their productivity, they find it difficult to produce coherent wholes. This study attempts to investigate EFL learners’ deficiencies in writing. The article opts for a mixed method of research whereby a questionnaire was architected to 50 second-year students from Badji Mokhtar Annaba University. For deepened outcomes, a group-focus interview was held with six (6) writing teachers from the same university. Results showed that the participants lack knowledge of appropriate vocabulary, grammar rules, syntax, tenses, and writing coherence.